Vacuum ultraviolet silicon photomultipliers applied to BaF2 cross-luminescence detection for high-rate ultrafast timing applications. (4th June 2021) - Gundacker, S; Pots, R H; Nepomnyashchikh, A; Radzhabov, E; Shendrik, R; Omelkov, S; Kirm, M; Acerbi, F; Capasso, M; Paternoster, G; Mazzi, A; Gola, A; et al.
Abstract: Inorganic scintillators are widely used for fast timing applications in high-energy physics (HEP) experiments, time-of-flight positron emission tomography and time tagging of soft and hard x-ray photons at advanced light sources. As the best coincidence time resolution (CTR) achievable is proportional to the square root of the scintillation decay time it is worth studying fast cross-luminescence, for example in BaF2 which has an intrinsic yield of about 1400 photons/MeV. However, emission bands in BaF2 are located in the deep-UV at 195 nm and 220 nm, which sets severe constraints on photodetector selection. Recent developments in dark matter and neutrinoless double beta decay searches have led to silicon photomultipliers (SiPMs) with photon detection efficiencies of 20%–25% at wavelengths of 200 nm. We tested state-of-the-art devices from Fondazione Bruno Kessler and measured a best CTR of 51 ± 5 ps full width at half maximum when coupling 2 mm × 2 mm × 3 mm BaF2 crystals excited by 511 keV electron–positron annihilation gammas. Using these vacuum ultraviolet SiPMs we recorded the scintillation kinetics of samples from Epic Crystal under 511 keV excitation, confirming a fast decay time of 855 ps with 12.2% relative light yield and 805 ns with 84.0% abundance, together with a smaller rise time of 4 ps beyond the resolution of our setup. The total intrinsic light yield was determined to be 8500 photons/MeV. We also revealed a faster component with 136 ps decay time and 3.7% light yield contribution, which is extremely interesting for the fastest timing applications. Timing characteristics and CTR results on BaF2 samples from different producers and with different dopants (yttrium, cadmium and lanthanum) are given, and clearly show that the the slow 800 ns emission can be effectively suppressed. Such results ultimately pave the way for high-rate ultrafast timing applications in medical diagnosis, range monitoring in proton or heavy ion therapy and HEP.